EFEKTIVITAS PAKAN DENGAN SUPLEMENTASI DAGING IKAN GABUS (Channa Striata) TERHADAP PERBAIKAN HISTOLOGIS DUODENUM TIKUS WISTAR SETELAH MENGALAMI PENGONDISIAN STRES FISIOLOGIS - Rudi Juandi Gultom; S Sunarno; Siti Muflichatun Mardiati (Jurnal Akademika Biologi, 2016)
Physiological Stress and nutritional deficiencies that followed excessive activity is a trigger factor disturbance structure and function of the duodenum. Organ in the duodenum has the ability to regenerate periodically after experiencing problems due to physiological stress. Nutrient content of feed determine organ regeneration process duodenum of the small intestine. This study was conducted to assess, analyze and determine the concentration of fish meat cork to increase in diameter, villous length, the thickness of the layer of the mucosa, submucosa and muscularis duodenum of Wistar rats after conditioning the physiological stress.This study used 20 male Wistar rats consisted of 5 treatments with 4 replications. The treatment in this study consisted of P0: control, test animals were conditioned stress followed six days of feeding without supplementation with fish meat cork; P1, P2, P3, and P4 are test animals that were conditioned stress for 6 days and fed with supplementation of fish meat cork for 14 days, respectively 5%, 10%, 15%, and 20% of the time after conditioning stress. This study uses a completely randomized design (CRD). The parameters measured in this study is the diameter, villous length and thickness of the layers of mucosa, submucosa, and muscularis duodenum of the small intestine. Data were analyzed using Analysis of Variance (ANOVA) followed by Duncan test with 95% significance level. The results of this study are feeding the fish meat cork can improve the structure of histologic duodenum after  stress conditioning and feeding with supplementation of fish meat cork with a concentration of 15% giving effect to increase in diameter, the length of villi, and the thickness of the lining mucosa, submucosa, and muscularis duodenum, respectively -turut 2520 μm, 576.34 μm, 506 μm, 123.34 μm and 72.34 μm respectively higher 23.43%, 46.37%, 45.26%, 50.31%, and 22 , 95% compared to controls. It concluded supplementation with fish meat cork in feed can be used to improve the structure and function of post-stress duodenum.Keywords: stress, supplements, duodenum, cork fish, Channa striata, Wistar